Pripravništvo profesorjev slovenščine v Sloveniji in Avstriji - Šebjanič, Maja (Jezik in slovstvo, 2014)
Internship is the planned and professionally managed practical training of beginner teachers to achieve independence in their work. As such, it means entering the profession and learning pedagogical skills. The organisation of internship differs from country to country. Both in Slovenia and Austria, entering the teaching profession is organised and regulated on the state level. Although the models are rather similar, they demonstrate differences in some aspects. The results of empirical research based on the experiences of secondary school teachers of Slovene during internship show some deficiencies in the way they are currently organised, and highlight possible modifications aimed at improving the process that introduces secondary school teachers of Slovene to their pedagogical work.
Keywords: Slovene; slovenščina; didactic method; didaktika; pripravništvo; učitelj začetnik; profesor slovenščine; zakonodaja; Slovenia; Slovenija; Austria; Avstrija